The effect of tax preparation expenses for employees: Evidence from Germany - Kay Blaufus; Frank Hechtner; Axel Möhlmann (Arbeitskreis Quantitative Steuerlehre (arqus), 2014)
Tax preparation firms advertise their services as a way to save taxes. To investigate this subject, we use a panel of German income tax accounting data, consisting of employees and other taxpayers with non-business income, to explore the relationship between expenses for tax preparation and tax liabilities. We find a negative link with expenses exceeding estimated tax savings. Specifically, one additional Euro yields an estimated tax savings of 72 cents in an OLS regression and 24 cents in a fixed-effects regression. This finding indicates that cross-section estimates are upward biased. The magnitude of the effect implies that tax preparation expenses are not worthwhile from a tax saving perspective alone. In consideration of time savings, combined tax and time savings also do not exceed expenses for any income quintile. The result is robust to various alternative specifications such that in no setting do the pecuniary and time savings exceed the tax preparation expenses. Overall, our findings suggest an important benefit of tax preparation expenses beyond tax and time savings.
Keywords: H24; H31; 330; response to taxation; tax advisors; tax return preparation; tax preparation expenses